Nanoparticle shapes by using Wulff constructions and first-principles calculations - Barmparis, Georgios D.; Lodziana, Zbigniew; Lopez, Nuria; Remediakis, Ioannis N. (Beilstein Journal of Nanotechnology, 2015)
Background: The majority of complex and advanced materials contain nanoparticles. The properties of these materials depend crucially on the size and shape of these nanoparticles. Wulff construction offers a simple method of predicting the equilibrium shape of nanoparticles given the surface energies of the material.Results: We review the mathematical formulation and the main applications of Wulff construction during the last two decades. We then focus to three recent extensions: active sites of metal nanoparticles for heterogeneous catalysis, ligand-protected nanoparticles generated as colloidal suspensions and nanoparticles of complex metal hydrides for hydrogen storage.Conclusion: Wulff construction, in particular when linked to first-principles calculations, is a powerful tool for the analysis and prediction of the shapes of nanoparticles and tailor the properties of shape-inducing species.
Keywords: density functional theory (DFT); hydrogen storage; multi-scale simulations; nanoparticles; surface energies; surfactants; Wulff construction